Thermoresponsive self-assembled elastin-based nanoparticles for delivery of BMPs - Bessa, Paulo C. (2010)
Elastin-like polymers are a new type of protein-based polymers that display interesting properties in the biomaterial field. Bone morphogenetic proteins (BMPs) are cytokines with a strong ability to promote new bone formation. In this work, we explored the use of elastin-like nanoparticles (average size 237.5±3.0 nm), created by thermoresponsive self-assembly, for the combined release of bone morphogenetic protein-2 (BMP-2) and bone morphogenetic protein-14 (BMP-14). These BMPs could be encapsulated at high efficiency into the elastin-like particles and delivered in a sustained way for 14 days. The activity of the growth factors was retained, as shown by the induction of ALP activity and osteogenic mineralization in C2C12 cells. Increased bioactivity was observed with a combined release of BMP-2 and BMP-14. This approach shows a significant potential for future tissue engineering applications in bone.